Learning with immigrant children, families and communities: the imperative of early childhood teacher education. Issue 1 (2nd January 2017) - da Silva Iddings, Ana Christina; Reyes, Iliana
Abstract: This article reports on a longitudinal study spanning over 5 years, involving the design and implementation of an early childhood teacher education program model that engages a critical-ecological theoretical approach, a funds of knowledge perspective, and design-based methodology. This project aimed to promote equitable education for all children, and especially for young immigrant children encountering situations of oppression within the national and local educational contexts in Arizona. In this teacher education program, families, community members, researchers, pre-service teachers and teachers worked together to develop new modes of curricular activity, new spaces, new relationships, and new forms of movement among participants, as well as new circulations of literacy artefacts.